PELEMBAGAAN PROGRAM UNIT PENGELOLAAN KEUANGAN DESA BENGKULU REGIONAL DEVELOPMENT PROJECT DESA MUARA PAYANG KABUPATEN BENGKULU SELATAN - Aminudin, Achmad (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2020)
This research was done in Muara Payang village, District of South Bengkulu, predominantly inhabited by Serawai Tribe. A key informant composed of UPKD committee, POKJA members and 10 members of UPKD were the unit of analysis to reveal the phenomenon investigated using purposive random sampling. Information from the field was obtained through methods of in-depth interview, group discussion, and observation. Data were analysed descriptive and qualitatively. The objective of this research was to reveal the patterns of this rural economic self-sufficiency and sustainability of UPKD program of Muara Payang village in order to improve the self-sufficiency and Institutionalization of UPKD program of Muara Payang village in order to improve the self-sufficiency ability of the targeted group in rural areas and the possibility of empowering it in order to develop the self-sufficiency of the rural community. Field data has shown a fairly high level of institutionalization of the program, indicated by the democratic leadership of the UPKD chair and all administrators. Also, the ability of target group members to explore and utilize local resources, provide time, energy, funds and thoughts in the implementation and development of the UPKD program continuously. Also the process of Productive Economic Activities, the formation of Pokmas and Identification of Activities, Funds Revolving, and productive economic activities are in accordance with the implementation guidence